RESILIENT AQUATIC FOOD SYSTEMS (RAqFS) FOR HEALTHY PEOPLE AND PLANET. STAKEHOLDER ENGAGEMENT WORKSHOP REPORT - ZAMBIA - Muzungaire, Lizzy; Chileya, Agness; Mapedza, Everisto D.; Siamudaala, Victor; Malambo, Tom; Chisopo, Andrew; Buisson, Marie-Charlotte (WorldFish, 2022)
The report describes the stakeholder engagement workshop convened to introduce the AqF Initiative (in particular the AquaPlans work package) to the traditional leaders, community representatives and stakeholders working within the Kafue flats. Participants were drawn from Royal Highnesses from seven chiefdoms of the Kafue flats, Community resource Board representatives, development agencies, extension officers from government line ministries, NGOs and the academia.